Factors determining the average price level: A combined microeconomic and macroeconomic approach - Tamara Todorova; Brikena Myftarallari (Economies, 2024)
We analyze various determinants of the average price level using a strictly mathematical approach. Starting with the microeconomic perspective, we review the effect of demand shifters such as consumer income and the level of advertising on the average price level in a simple partial market equilibrium model. Then, we discuss the effect of supply shifters such as the exogenous tax level, worker wage, rental rate, and technology. We use implicit differentiation and Jacobian determinants. While government spending triggers inflation, taxes have the opposite effect. This is consistent with Keynesian theory. Money supply increases national income and prices while reducing the equilibrium interest rate. Therefore, money supply has pro-inflationary effects. The effect of money demand is the opposite-it increases the equilibrium interest rate, thereby lowering national income and prices. Augmenting the model to the level of international trade, we find that exports raise national income, the interest rate, and the average price level, while the effect of imports is just the opposite. Government spending raises the exchange rate while continuous inflation lowers it.
Keywords: 330; exports multiplier; government spending; inflation; taxes